Perbedaan Kemandirian Lansia di Rumah dan di PSLUPare Kabupaten - Febrin Eko; Ratna Hidayati; Widyasih Sunaringtyas (STIKES Karya Husada Kediri, 2018)
Elderly is a part of the process of human growth, part of the life process that can not be avoided and will beexperienced by every individual, the elderly will experience physical changes that affect his independence inconducting activity of daily living, mental status, economic and social interaction. This study aims to determinethe differences of independence of the elderly living in the village Tulungrejo pare district and who live in PSLUPare Kediri District. Researchers use quantitative research type with comparative design. The sample consists of140 respondents consisting of 70 respondents who live in Tulungrejo village and 70 respondents who live inPSLU Pare Kediri Regency with Cluster Sampling and Purposive Sampling technique. Statistical analysis usingMann-Whitney test with α = 0.05. The results showed that the elderly living at home is good independence of26.25% while those living in the PSLU are moderate independence of 25%. After the test using Mann-WhitneyTest in get ρ value = 0,000 with α = 0.05 which means there is a difference of independence of elderly who live athome and live in PSLU Pare Kediri Regency. The existence of differences in the independence of the elderly dueto adjustment factors to changes that occur in him. Suggestion from this research is family or party PSLU givemore support and spirit to elderly so elderly can improve quality of life.